The Effect of Celery Leaf Decoction (Apium Graveolens) on Lowering Blood Pressure in Elderly Hypertensive Patients - Nuraini; Sunarmi; Hendri Tamara Yuda; Armi; Neng Annis Fathia (CV. Get Press Indonesia, 2025)
Hypertension is a major risk factor for cardiovascular disease, with increasing prevalence globally and nationally. Alternative treatments such as celery leaves (Apium graveolens), which contain active compounds with antihypertensive effects through vasodilation and diuretic mechanisms, are being explored. Purpose: This study aimed to determine the effect of celery leaf decoction on systolic and diastolic blood pressure reduction in elderly individuals with hypertension. Methods: A quasi-experimental pretest-posttest design was used on 30 elderly patients with mild to moderate hypertension in RW III Anduring, Padang (2025). Participants consumed 250 mg of celery leaf decoction twice daily for 14 days. Data were analyzed using a paired t-test with a significance level of p < 0.05. Results: The average systolic blood pressure decreased from 147.6 mmHg to 133.4 mmHg (p = 0.000). The diastolic pressure dropped from 92.3 mmHg to 85.1 mmHg (p = 0.001), indicating a statistically significant effect. Conclusion: Celery leaf decoction effectively lowers blood pressure in elderly hypertensive patients and may serve as a complementary therapy to reduce reliance on antihypertensive drugs. Implications: Health workers, especially at Puskesmas, are encouraged to educate communities on the potential of herbal remedies like celery leaf as part of integrative hypertension management.